Kebijakan Distribusi dalam Pembangunan Ekonomi Islam - Naerul Edwin Kiky Aprianto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Economic growth cannot be separated from justice of distribution for each individual. But in reality, it seems an injustice and inequality in the distribution of income and wealth, so the impact on the increase of poverty. Distribution policy in economic development Islam upholds the values of justice based on the Qur’an, that is wealth does not circulate only one group alone. This paper concludes that the distribution policy in economic development Islam emphasizes the elimination rate system that benefits those who have capital and resulted in accumulation of wealth in certain groups. In addition, people are required to realize the importance of creating the role of distributive justice and narrow the economic gap with the practice regular charity, infaq, sadaqah, awqaf, inheritance and others, so that it can be optimized as a source of financing economic development. Then, the no less important in the distribution policy is to optimize the sukuk to finance the country’s development in order to improve public services, so that the results can be felt by the whole society.